2020
DOI: 10.3390/ijerph17239062
|View full text |Cite
|
Sign up to set email alerts
|

Diet Quality Compared to the Nutritional Knowledge of Polish, German, and Slovakian University Students—Preliminary Research

Abstract: The eating habits of students differ significantly from those recommended by health practitioners. The aim of this study was to find differences related to diet quality and knowledge on nutrition among Polish, German, and Slovakian students as well as to examine which factors differentiate the diet quality of students from these three countries. The study was conducted on a group of 394 university students from Poland, Germany, and Slovakia. The assessment of diet quality and knowledge on food and nutrition wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 46 publications
1
15
1
3
Order By: Relevance
“…In general, medical university students should gain more knowledge about the benefits and necessity of healthy habits. These findings are not in accordance with the results observed in previous research, which suggested that the highest level of knowledge on food and nutrition was not connected with a healthier diet [16,17]. Other studies revealed that even students from medical and nutritional university departments showed inadequate awareness on healthy eating habits [16] and did not fulfil the PA and nutritional recommendations [19].…”
Section: Discussioncontrasting
confidence: 80%
See 4 more Smart Citations
“…In general, medical university students should gain more knowledge about the benefits and necessity of healthy habits. These findings are not in accordance with the results observed in previous research, which suggested that the highest level of knowledge on food and nutrition was not connected with a healthier diet [16,17]. Other studies revealed that even students from medical and nutritional university departments showed inadequate awareness on healthy eating habits [16] and did not fulfil the PA and nutritional recommendations [19].…”
Section: Discussioncontrasting
confidence: 80%
“…The nutrition and level of physical activity of university students were alarming and unsatisfying before the pandemic [16,17]. In previous years, there has been a rise in the westernisation of diet among this population [18].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations